Factors linked to virological failure in people on a dolutegravir-based regimen in Mamelodi - Moloko S. Mmatsoku; Sanele Ngcobo (Southern African Journal of Infectious Diseases, 2024)
Background: Since 2019, the World Health Organization has recommended dolutegravir-containing regimens for HIV in low- and middle-income countries because of its high genetic barriers to resistance, lower drug interactions, fewer side effects, higher viral load (VL) suppression rates and cost-effectiveness compared to efavirenz.